Intertwingled The Work and Influence of Ted Nelson - Dechow, Douglas R.; Struppa, Daniele C. (History of Computing,, 2015)
This engaging volume celebrates the life and work of Theodor Holm "Ted" Nelson, a pioneer and legendary figure from the history of early computing. Presenting contributions from world-renowned computer scientists and figures from the media industry, the book delves into hypertext, the docuverse, Xanadu, and other products of Ted Nelson's unique mind. Topics and features: Includes a cartoon and a sequence of poems created in Nelson's honor, reflecting his wide-ranging and interdisciplinary intellect Presents peer histories, providing a sense of the milieu that resulted from Nelson's ideas Contains personal accounts revealing what it is like to collaborate directly with Nelson Describes Nelson's legacy from the perspective of his contemporaries from the computing world and the scholars who continue to examine his work Provides a contribution from Ted Nelson himself With a broad appeal spanning practitioners in computer science, historians of science and the general reader, this inspiring collection reveals the continuing influence of the original visionary of the World Wide Web. Prof. Daniele C. Struppa is Chancellor of Chapman University, Orange, CA, USA. His other publications with Springer include the titles The Mathematical Legacy of Leon Ehrenpreis and Noncommutative Functional Calculus. Dr. Douglas R. Dechow is Digital Humanities and Science Librarian at Chapman University Leatherby Libraries.